MLL2 is required in oocytes for bulk histone 3 lysine 4 trimethylation and transcriptional silencing. - Claudia V Andreu-Vieyra; Ruihong Chen; Julio E Agno; Stefan Glaser; Konstantinos Anastassiadis; A Francis Stewart; Martin M Matzuk (PLoS Biology, 2010)
During gametogenesis and pre-implantation development, the mammalian epigenome is reprogrammed to establish pluripotency in the epiblast. Here we show that the histone 3 lysine 4 (H3K4) methyltransferase, MLL2, controls most of the promoter-specific chromatin modification, H3K4me3, during oogenesis and early development. Using conditional knockout mutagenesis and a hypomorph model, we show that Mll2 deficiency in oocytes results in anovulation and oocyte death, with increased transcription of p53, apoptotic factors, and Iap elements. MLL2 is required for (1) bulk H3K4me3 but not H3K4me1, indicating that MLL2 controls most promoters but monomethylation is regulated by a different H3K4 methyltransferase; (2) the global transcriptional silencing that preceeds resumption of meiosis but not for the concomitant nuclear reorganization into the surrounded nucleolus (SN) chromatin configuration; (3) oocyte survival; and (4) normal zygotic genome activation. These results reveal that MLL2 is autonomously required in oocytes for fertility and imply that MLL2 contributes to the epigenetic reprogramming that takes place before fertilization. We propose that once this task has been accomplished, MLL2 is not required until gastrulation and that other methyltransferases are responsible for bulk H3K4me3, thereby revealing an unexpected epigenetic control switch amongst the H3K4 methyltransferases during development.